Esfuerzos sobre periodonto sano en alineadores dentales power-ridge en incisivo lateral superior. Estudio elementos finitos (2022)
To compare the distribution and values of the stress produced in the healthy periodontium, when applying different forces 100 gr, 200gr and 400gr in the torque movement with power-ridge in the upper right lateral incisor with mechanical dental aligners in a study of finite element method (FEM).